Biodegradation of Sulfonated Lignite (SL) by fungi from waste drilling mud. Issue 1 (November 2020) - Liu, Hanjun; Chen, Qiang; Huang, Min; Chen, Lirong; Jiang, Xuebin; Wang, Entao; Liu, Yihao; Leng, Xuemei; Xie, Liang; Zhao, Ke; Gu, Yunfu; Yu, Xumei; et al.
Abstract: In this paper, three indigenous Sulfonated lignite (SL) degrading fungi were isolated from waste drilling mud (WDM) and were identified, and the mechanism of SL degradation and potential of WDM bioremediation was presented. These SL degrading fungi (WNF15, WNF20, and WNF22) were as Pseudallescheria ellipsoidea, Stachybotrys chartarum, and Scopulariopsis brevicaulis by their physiological characteristics and ITS gene sequencing. SL degradation test results showed that all three species can effectively degrade SL but WNF-20 had the highest SL degradation ratio (47.54%). MnP and Lac were the dominant enzymes used by the fungi for SL degradation. Analysis of SO4 2- concentration and degradation products suggested that the fungus firstly breaks the C-SO3 bond and release of sulfite assisted. Subsequently, breaks the branched-chain and crosslink bone of the aromatic rings in desulphurisation by-products, and then the broken crosslink bone were transformed into hydrocarbons and aromatic acids. Inoculation of a mixture of the three fungi into a liquid MS medium containing 5% WDM resulted in a chemical oxygen demand removal ratio of 87.65% after 14 d. All rustles suggest that these three fungi are efficient SL degraders and can be used for bioremediation of WDM in gas drilling fields.